The Role of Ushul At-Tarbiyah Al-Islamiyyah in Enhancing Motivation to Learn Arabic - Umar Najih Zein; Annisa Salsabilla Rohadatul 'Aisy; M. Kholis Amrullah (Quality : Journal Of Education, Arabic And Islamic Studies, 2026)
This study aims to examine the role of Ushūl at-Tarbiyah al-Islāmiyyah in enhancing students’ motivation to learn Arabic. The study focuses on three main aspects: the fundamental principles of Islamic education relevant to Arabic language learning, the forms of implementation of these principles in the learning process, and their contribution to fostering students’ learning motivation. This research employs a library research approach by reviewing various academic sources, including books, journal articles, and scholarly works related to Islamic educational principles, learning motivation, and Arabic language education. Data were analyzed using content analysis to identify, classify, and synthesize relevant concepts. The findings indicate that Ushūl at-Tarbiyah al-Islāmiyyah, through the integration of ta‘līm and ta’dīb, plays a significant role in strengthening students’ motivation to learn Arabic. Ta‘līm supports structured, systematic, and meaningful instruction, while ta’dīb fosters learning ethics, respect for knowledge, and value awareness, leading to the development of intrinsic motivation. This study contributes theoretically by offering a conceptual foundation for Arabic language learning that is pedagogically effective and spiritually meaningful.